2016
DOI: 10.3892/ol.2016.5087
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TP53 and TP16 expression in human papillomavirus-associated non-small cell lung cancer

Abstract: Human papilloma virus (HPV) infection has previously been reported to be associated with TP53 and TP16 expression in Japanese and Taiwanese patients with lung cancer, but data for advanced non-small cell lung cancer (NSCLC) patients is limited. The present study examined the association between HPV infection and TP53 and TP16 expression in Chinese patients with advanced NSCLC. HPV DNA was detected in 20 out of 83 (24%) lung tumors, and was observed more frequently in non-smokers, patients with lymph node metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, HPV16 E6 but not E7 oncoprotein induced extracellular regulated protein kinase (ERK) signaling pathway to enhance HIF‐1α accumulation . HPV E6 protein also bound cell cycle regulator TP53 to trigger degradation, promote proliferation, and inhibit apoptosis of NSCLC cells . Moreover, several studies revealed that Toll‐like receptors (TLRs) were involved in HPV‐induced squamous cell carcinoma, and higher expression of nucleic acid‐sensing TLRs predicted HPV16 clearance and associated with E6‐directed cell‐mediated response .…”
Section: Introductionmentioning
confidence: 99%
“…However, HPV16 E6 but not E7 oncoprotein induced extracellular regulated protein kinase (ERK) signaling pathway to enhance HIF‐1α accumulation . HPV E6 protein also bound cell cycle regulator TP53 to trigger degradation, promote proliferation, and inhibit apoptosis of NSCLC cells . Moreover, several studies revealed that Toll‐like receptors (TLRs) were involved in HPV‐induced squamous cell carcinoma, and higher expression of nucleic acid‐sensing TLRs predicted HPV16 clearance and associated with E6‐directed cell‐mediated response .…”
Section: Introductionmentioning
confidence: 99%